Zoom! - Munsch, Robert N., 1945-; Martchenko, Michael (New York : Cartwheel Books, 2003)
When Lauretta tries out a 92-speed, silver and gold, dirt-bike wheelchair, she gets a speeding ticket but also helps out her brother.
Keywords: Wheelchairs -- Fiction; Speed -- Fiction